Georgia O’Keeffe – the cross in the New Mexico landscape - Makówka, Leszek (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
The criticism of Georgia O’Keeffe’s output focuses on abstract paintings. The author of the paper states that numerous paintings by O’Keeffe with the motif of the cross against the New Mexico landscape constitute an equally important part of her work, unknown to a broader audience. An attempt at the reconstruction of the history of the creation of the paintings, conducted on the basis of texts by their author and her contemporary critics, proves that the sign of the cross in those paintings plays a key role both in the compositional and ideological aspects. At the same time, in respect of formal solutions, those works equal the well-known paintings by the artist created as a result of transformation of a realistic subject.

Krytyka dorobku Georgii O’Keeffe skupia się na obrazach abstrakcyjnych. Autor artykułu stawia tezę, że liczne obrazy O’Keeffe z motywem krzyża na tle pejzażu Nowego Meksyku stanowią równie ważny dział jej twórczości, nieznany szerszej grupie odbiorców. Próba rekonstrukcji historii powstawania obrazów przeprowadzona na podstawie tekstów autorki oraz ówczesnej krytyki dowodzi, że znak krzyża w tych obrazach odgrywa kluczową rolę zarówno na płaszczyźnie kompozycyjnej, jak i ideowej. Jednocześnie prace te dorównują pod względem rozwiązań formalnych znanym obrazom artystki powstałym w efekcie przekształcenia realistycznego tematu.
Georgia O’Keeffe – krzyż w pejzażu Nowego Meksyku
Translated by Agnieszka Gicala
Keywords: Georgia O’Keeffe; New Mexico; painting; landscape; cross; Nowy Meksyk; obraz; pejzaż; krzyż